Evaluation of Project Based Learning in the Context of Mathematical Ability Development - Nasution, Izza fadhila (Lembaga Riset Mutiara Akbar, 2023)
This research discusses the implementation and evaluation of project-based learning in the context of developing mathematical abilities at certain educational levels. This learning approach aims to improve understanding of mathematical concepts, problem solving skills, and collaborative abilities through a learning approach that involves real projects. The research used includes learning design, material selection, and ongoing evaluation. The results of this study showed significant improvement and proficiency in students' mathematics, accompanied by a positive response to the project-based learning experience. The conclusion highlights the positive contribution of project-based learning and its better integration in the mathematics education context.